Heat Shock Protein Member 8 Is an Attachment Factor for Infectious Bronchitis Virus - Zhu, Pengpeng; Lv, Chenfei; Fang, Chengxiu; Peng, Xing; Sheng, Hao; Xiao, Peng; Kumar Ojha, Nishant; Yan, Yan; Liao, Min; Zhou, Jiyong (Frontiers in Microbiology, 2020)
Although infectious bronchitis virus (IBV) is the first coronavirus identified, little is known about which membrane protein of host cells could interact with IBV spike protein and facilitate the infection by the virus. In this study, by using a monoclonal antibody to the S1 protein of IBV M41 strain, we found that heat shock protein member 8 (HSPA8) could interact with spike protein of IBV. HSPA8 was found to be present on the cell membrane and chicken tissues, with highest expression level in the kidney. Results of co-IP and GST-pull-down assays indicated that the receptor binding domain (RBD) of IBV M41 could interact with HSPA8. The results of binding blocking assay and infection inhibition assay showed that recombinant protein HSPA8 and antibody to HSPA8 could inhibit IBV M41 infection of chicken embryonic kidney (CEK) cells. Further, we found that HSPA8 interacted with the N-terminal 19–272 amino acids of S1 of IBV Beaudette, H120 and QX strains and HSPA8 from human and pig also interacted with IBV M41-RBD. Finally the results of binding blocking assay and infection inhibition assay showed that recombinant HSPA8 protein and antibody to HSPA8 could inhibit IBV Beaudette strain infection of Vero cells that were treated with heparanase to remove heparan sulfate from the cell surface. Taken together, our results indicate that HSPA8 is a novel host factor involved in IBV infection.